Relationship between spatial distribution of chaetognaths and hydrographic conditions around seamounts and islands of the tropical southwestern Atlantic - SOUZA,CHRISTIANE S. DE (2014)
Relationship between spatial distribution of chaetognaths and hydrographic conditions around seamounts and islands off Northeastern Brazil were analyzed from 133 oceanographic stations during the months of January – April of 1997 and April – July of 1998. Oblique zooplankton tows, using 50 cm diameter Bongo nets with 500µm mesh with a flowmeter to determine the filtered volume, were carried out to a maximum of 200m depth. The Superficial Equatorial Water, which had a salinity > 36 PSU and temperature > 20°C, occupied the top 80 to 200m depth. Below this water mass was the South Atlantic Central Water with salinity ranging from 34.5 to 36 PSU and temperature from 6 to 20°C. The community of chaetognaths showed six species: Pterosagitta draco, Flaccisagitta enflata, Flaccisagitta hexaptera, Pseudosagitta lyra, Serratosagitta serratodentata, and Sagitta helenae. Of these species, F. enflata was the most abundant (32.05% in 1997 and 42.18% in 1998) and the most frequent (87.88% in 1997 and 95% in 1998) during both periods. A mesopelagic specie was identified (P. lyra). This specie was more abundant in 1997 (3.42%), when the upwelling was more intense. P. lyra occurred in 22% of the samples during 1997. The abundance of F. enflata, an epiplanktonic species, increased, associated with greater water-column stability.